2023
DOI: 10.1021/acs.jpcc.2c07661
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alumina Supported Pt-SnO2 Hybrid Nanostructures by In Situ Transformation of PtSn Alloy Nanoparticles and Their Application as Highly Efficient Catalysts for Selective Hydrogenation of Furfural

Abstract: In this work, PtSn alloy nanoparticles were synthesized by coreduction of Pt and Sn precursors by ethylene glycol in the presence of stabilizing agents and then were in situ transformed into Pt-SnO 2 hybrid nanostructures on alumina supports by calcination. Relative to Pt/Al 2 O 3 , Pt 1 -(SnO 2 ) 0.3 / Al 2 O 3 demonstrates improved catalytic efficiency for furfuryl alcohol production by furfural hydrogenation. Under the H 2 pressure of 1.0 MPa, 100 °C, 3.0 h, and furfural/Pt molar ratio of 1435/1, the furfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…As shown in Table1 entry 24, Wang et al reported a 99.7 % FF conversion and 98.5 % FA selectivity was obtained by reacting Pt 1 (SnO 2 ) 0.3 / Al 2 O 3 catalyst with isopropanol as solvent at 100 °C for 3.0 h under 1.0 MPaH 2 . [30] The catalyst was synthesized by coreduction of Pt and Sn precursors by ethylene glycol in the presence of stabilizing agents and then were in situ transformed into PtÀ SnO 2 hybrid nanostructures on alumina supports by calcination. Sn(0) itself does not possess intrinsic hydrogenation activity, but the synergistic interaction between Pt and SnO 2 could change the electronic and geometrical structure of Pt atoms, thus improving the catalytic performance in the preparation of FA from FF hydrogenation.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table1 entry 24, Wang et al reported a 99.7 % FF conversion and 98.5 % FA selectivity was obtained by reacting Pt 1 (SnO 2 ) 0.3 / Al 2 O 3 catalyst with isopropanol as solvent at 100 °C for 3.0 h under 1.0 MPaH 2 . [30] The catalyst was synthesized by coreduction of Pt and Sn precursors by ethylene glycol in the presence of stabilizing agents and then were in situ transformed into PtÀ SnO 2 hybrid nanostructures on alumina supports by calcination. Sn(0) itself does not possess intrinsic hydrogenation activity, but the synergistic interaction between Pt and SnO 2 could change the electronic and geometrical structure of Pt atoms, thus improving the catalytic performance in the preparation of FA from FF hydrogenation.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…Currently, FF hydrogenation catalysts for the preparation of FA are mainly divided into two categories: noble metal‐based catalysts (Pd, Pt, Ru, Ir, etc. ) [11a,30,32] and non‐noble metal‐based catalysts (Cu, Ni, Co, etc.) [1a,17a,33] .…”
Section: Conversion Of Ff To Renewable Value‐added Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…(v) Platinum-tin (Pt-Sn) nanoparticles: Zhou et al [53] synthesized PtSn alloy nanoparticles through the co-reduction of Pt and Sn precursors along with stabilizing agents. Subsequently, these nanoparticles underwent an in situ trans-formation into Pt-SnO2 hybrid nanostructures on alumina supports through calcination.…”
Section: B Bimetallic and Alloy Nanoparticlesmentioning
confidence: 99%
“…A series of strategies have been developed to promote the conversion rate and control the product selectivity, such as the modification of active metal sites through the choice of supports, the addition of promoters, steric effects, even improved catalyst preparation and adjusted reaction conditions, etc . In the past decades, the performance of Pt-, Pd-, Ru-, and Rh-based catalysts for this reaction has been extensively reported by many groups. Noble metal catalysts have been demonstrated to have higher efficiency in producing hydrocinnamaldehyde (HCMA) and hydrocinnamyl alcohol (HCMO) compared to CMO due to their superior hydrogen dissociation ability and ease of –CC– bond activation. Therefore, selectivity is generally difficult to control.…”
Section: Introductionmentioning
confidence: 99%